Enhanced four-wave mixing with polymer-coated Iron phosphorus trisulfide (FePS3) arc-shaped fiber - Ahmad, H. (Springer, 2023)
Four-wave mixing (FWM) was demonstrated using polymer-coated Iron phosphorus trisulfide (FePS3) arc-shaped fiber as a device for nonlinear application. The FWM-based system had a maximum FWM conversion efficiency and wavelength tuning range of -37.5 dB and 6 nm, respectively. The FWM-based laser output was highly stable, with a maximum fluctuation in FWM conversion efficiency of only 0.1 dB. The overlaying of low refractive index (RI) polymer on the FePS3 arc-shaped fiber enhanced the device's performance, with an effective nonlinear coefficient, gamma, of the device was calculated to be 666.7 W-1 km(-1). The proposed nonlinear device is an exciting device for integration in optical network applications.